Hubungan Karakteristik Pekerja Dengan Praktik Penerapan Prosedur Keselamatan Kerja Di PT. Bina Buna Kimia Ungaran - Kurniawan, Bina; Lestantyo, Daru; Murtiningsih, Dewi (Jurnal Promosi Kesehatan Indonesia, 2006)
Background : Occupational health and safety procedures have been developed by Environmental Health and Safety Department in PT. Bina Buna Kimia Ungaran Safety procedures were developed in order to control the potential hazards and minimize occupational accidents which caused by human factors. Unfortunately, many workers have neglected tooperate the procedures correctly. This study identifies the relationships between worker’s characteristics such as age, sex, educational level, working period, knowledge, attitudes, and the practice of workers.Method : Thirty eight temporary workers from production section have participated in this study. They were selected using a simple random sampling. A scheduled-structured questionnaire with a face to face interview has been used to collect the data. Meanwhile, anobservation using check lists has also been used to observe worker’s behaviour in operating safety health procedures.Results : The study found that there are no associations between sex, working period and the practice of safety procedure of the respondents. However, age and education level of workers have significant relationships. Likewise, knowledge and attitudes of respondents have alsoassociations with the practice of safety procedures of the respondents. This study suggests that the information of safety procedures including the positive and negative effects of these should be conducted regularly to motivate the workers.Keywords: Worker, occupational health, Safety procedures, Behaviour